2022
DOI: 10.1021/acsaem.1c03989
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Two Different ZnO Addition Strategies on the Sinterability and Conductivity of the BaZr0.4Ce0.4Y0.2O3−δ Proton-Conducting Ceramic Electrolyte

Abstract: A comparative study has been made to relate the effect of different addition strategies for the sintering aid of ZnO (∼1 wt %) on the performance of the BaZr0.4Ce0.4Y0.2O3−δ (BZCY442) electrolyte in order to improve the sinterability and conductivity of this material more efficiently. Two samples, Zn-doped BaCe0.4Zr0.4Y0.15Zn0.05O3−δ (BZCYZn, internal doping) and BZCY–ZnO (BZCY442 mixed with ZnO, external addition), were synthesized. The BZCYZn crystallized at a single phase after sintering at 1350 °C, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…This decrease can be attributed to the higher mobility of holes and proton dehydration in the structure. 50 This phenomenon also extends a possible explanation for the decrease in the OCV value. We performed an EIS of the cell under OCV conditions to isolate the resistance contribution (ohmic resistance, R o ; polarization resistance, R P ) in the constructed cell.…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…This decrease can be attributed to the higher mobility of holes and proton dehydration in the structure. 50 This phenomenon also extends a possible explanation for the decrease in the OCV value. We performed an EIS of the cell under OCV conditions to isolate the resistance contribution (ohmic resistance, R o ; polarization resistance, R P ) in the constructed cell.…”
Section: Resultssupporting
confidence: 65%
“…The MPD of this study is well comparable with the LCO and BZCY-based electrolyte. 5,26,50,52–54 This research demonstrates enhancement in MPD when compared to the La 1.85 Y 0.15 Ce 2 O 7 electrolyte-based SOFC. 31 However, it should be noted that some literatures have reported high performances, which are based on doped LCO; for example, Zhang et al 1 achieved the MPD of 1031 mW cm −2 at 700 °C and Wu et al 8 reported the MPD of 897 mW cm −2 at 700 °C by utilizing La 1.85 Mg 0.15 Ce 2 O 7− δ electrolyte.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…Therefore, lowering their sintering temperature while maintaining high proton conductivity is critical for PCC practical application . Adding sintering aids such as NiO, ZnO, etc., is an effective strategy to increase the sintering activity of BZCY proton conducting electrolytes. For instance, after adding NiO, BZCY sintered with NiO at 1400 °C has a higher proton conductivity and a comparable relative density to the bare one sintered at 1600 °C . Nonetheless, it usually results in some degree of electronic conductivity, especially at high temperatures.…”
mentioning
confidence: 99%